Upper limit of available water in field as related to laboratory-determined parameters - SATYAVATHI, P L A (The Indian Journal of Agricultural Sciences, 2013)
The upper limit of available water (field capacity) was measured in situ, which is the water content at which drainage from a prewetted soil had practically ceased. The field-measured limits were compared to laboratory-estimated values of moisture retention at 10 and 33 k Pa, using core, clod, crushed and sieved soil samples. A significant correlation (1=>= 0.9) was found between in-situ field capacity ,and moisture retained at 10 or 33 kPa. The derived regression equations can be applied to improve the laboratory estimates of fleld capacity.